Removal of Cu(II) ions from aqueous solutions using membrane system and membrane capacitive deionization (MCDI) technology - Cetinkaya, Afsin Y.; Bilgili, Levent (SPRINGER, 2021)
Copper ion removal with nanofiltration membranes has accelerated in recent years. In this study, Cu2+ ion removal was investigated with nanofiltration membrane and a membrane capacitive deionization (MCDI) system; consequently, it was observed that the highest performance was seen when these two systems worked in an integrated system (99% Cu2+ ion removal) MCDI system is a purification technology through ion exchange membranes based on applying an electric field between two opposed electrodes. The flow rate, direct current voltage, and the operation time at which the Cu2+ ion removal rate was the highest were 50 mL/min, 1.2 V, and 15 min. respectively. Here, we report the application of the life cycle assessment (LCA) method to evaluate the environmental performance of the membrane system in different operating conditions. In the sensitivity analysis component of the study, different materials used in the membrane system and MCDI ststem were compared. Results from the LCA analysis showed that the MCDI system has far worse environmental impacts in all aspects particularly in material and energy-related effects.
Keywords: Membrane capacitive deionization; Cu (II) removal; Life cycle assessment; Environmental impacts; HEAVY-METAL IONS; WASTE-WATER; REVERSE-OSMOSIS; NANOFILTRATION; BIOREACTOR; HEALTH; Environmental Sciences & Ecology